Steering Spin Fluctuations in Lattice Systems Via Two-Tone Floquet Engineering - Romero-Huenchunir, G; Peña-Bernales, R (Institute of Physics, 2025)
We report on the control of spin pair fluctuations using two-tone Floquet engineering. We consider a one-dimensional spin-1/2 lattice with periodically modulated spin exchanges using parametric resonances. The stroboscopic dynamics generated from distributed spin exchange modulations lead to spin pair fluctuations reaching quasi-maximally correlated states and a subharmonic response in local observables, breaking the discrete-time translational symmetry. We present a protocol to control the interacting many-body dynamics, producing spatial and temporal localization of correlated spin pairs via dynamically breaking correlated spin pairs from the edges towards the center of the lattice. Our result reveals how spin fluctuations distribute in a heterogeneous lattice depending on parametric resonances. This may open new routes for exploring distinct nonequilibrium states of matter and the conduction of quasiparticles in quantum materials. © 2024 IOP Publishing Ltd. All rights, including for text and data mining, AI training, and similar technologies, are reserved.